Relationships between job satisfaction, job motivation, organizational commitment and intent to stay among academic staff of private colleges - Morshidi, Azizan (2000)
Job attitudes research in private education sector is limited in Malaysia. This study examines the relationships between Job Satisfaction, Job Motivation, Organizational Commitment and Intent to Stay among Academic Staff of Private Colleges. The issues of job attitudes is important any industry and this study focuses on the job attitudes among the private college academic staff. Comprehensive review of related literatures leads to a formation of a theoritical framework. Three main research questions to be answered in this study are to find the levels of job satisfaction, job motivation, organizational commitment and intention to remain of the academic staff, to find out whether the job satisfaction and job motivation of teaching workforce relate to their commitment, and does the organizational commitment relate to their intention to remain. Another question addressed is the magnitude of these relationships of these work attitudes. Based on this design, three null hypotheses have been forwarded. This research have been carried out in Kuching, Sarawak. 141 academic staff have been responded to survey. The analysis tackles two types of analysis: descriptive analysis and inferential analysis. The researcher utilized several methods such as boxplits, normal plots, chi-square test, z-test, Pearson Product Moment Correlation, Partial Correlation, ANOVA, multiple regression and OLAP extractions in order to arrive with interpretation of the findings. Based on the analysis, all three null hypotheses are rejected. The study finds, basically, that job motivation emerges as the best predictor of organizational commitment and all the relationships between the job attitudes in hands are positive in nature. In this study, while the organizational commitment positively relates with intent to remain in the organization, the degree of importance is rather secondary. Several implications of the study have been outlined particularly for the private education industry and theoretical perspectives of the subject matter. This study also covers the research limitations and recommendations for the management and future research interest.